PERSPEKTIF ANTROPOLOGI BUDAYA TRADISI BARITAN MOMENT KEBERSAMAAN DALAM DO’A DALAM PERGANTIAN TAHUN BARU HIJRIYAH - Maskur, maskur; Masnida, Masnida (JKaKa:Jurnal Komunikasi dan Konseling Islam, 2024)
Activities Traditions of glorifying/glorifying the month of Muharam/Suro by Indonesian people regardless of ethnicity, belief (religion) in various regions, both urban and rural communities in parts of the Indonesian nation, carry out various activities or activities that vary according to their respective local wisdom. With the increasing richness of the cultural traditions of Indonesian society, Islam is colored by Islam as the religion adhered to by the majority of society. The contact between Islam and local culture has led to a diversity of traditions with Islamic nuances. Traditions in the month of Muharram in Indonesian society, which are generally carried out on Muharram 1-10, are represented in various forms and various activities. In Sumberagung Pesanggaran and in general the Indonesian community enters the 1st to 10th of Muharom or sweet Friday night (legi) there is a tradition of giving alms takiran/kotaan rice, market snacks, making porridge/jenang suro, giving donations to orphans, the poor. This article describes the diversity of community activity traditions during the month of Muharram/Suro from a historical and cultural perspective